First, multiplying the second equation by 9, we get:
9x + 27y = -216
Then, adding the first equation to this new equation, we get:
- 9x - 7y + 9x + 27y = 22 - 216
20y = -194
y = -194/20
y = -9.7
Substitute this value back into the second equation:
x + 3*(-9.7) = -24
x - 29.1 = -24
x = -24 + 29.1
x = 5.1
Therefore, the solution is (5.1, -9.7) which can also be written as (51/10, -97/10)
Use the elimination method to solve the follow system of equations.
9x−7y=22
x+3y=−24
This question requires you to show your work.
(1 point)
Responses
(0,−8)
open paren 0 comma negative 8 close paren
(4, 2)
(4, 2)
(−3,−7)
open paren negative 3 comma negative 7 close paren
(3,−9)
1 answer